The secondary electron yields and related surface properties evolution of laser treated stainless steel induced by different ultrasonic cleaning duration. (28th June 2021) - Wang, J.; Wu, Y.; You, Z.; Gao, Y.; Zhang, J.; Zhang, T.; Hu, Y.; Wang, S.; Li, H.; Xu, Z.; Liu, Y.; Li, W.
Abstract: As a novel method, laser treatment was proposed to be applied on the surface modification of stainless steel 316L commonly used in accelerator vacuum system to mitigate the secondary electron emission. However, the final property of the material surfaces, especially the secondary electron yield (SEY) property depends on a rather large number of factors, among them are the surface cleaning scenarios needed before installation. In particular, the surface morphologies and surface chemical states may be changed during the ultrasonic cleaning used for laser treated stainless steel surfaces. Therefore, the influence of ultrasonic cleaning duration on the surface composition, surface morphology and secondary electron characteristics of stainless steel were studied for the first time. The secondary electron yield test results demonstrated that the maximum SEY ( δ max ) of laser treated stainless steel samples increased with the increase of ultrasonic cleaning time. After ultrasonic cleaning in acetone and absolute ethyl alcohol each for 3 minutes, 10 minutes and 15 minutes, respectively, the δ max of laser treated stainless steel samples increased about 0.7%–1.7%, 1.3%–2.4% and 4.9%–15.3%, respectively, compared with that of uncleaned laser treated ones. The surface morphologies, surface roughness, surface chemical states related to the SEY evolution were also evaluated and analyzed.